Using captive seabirds to assess knowledge gaps in stable isotope analysis of diets - Micklem, Isabel Andrea (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2019)
Stable isotope (SI) ratios of carbon (Î´13C) and nitrogen (Î´15N) are now widely used as biomarkers in ecological studies to provide information about food web structuring. However, understanding trophic relationships using SI analysis requires not only knowledge of SI values of predator and prey, but also accurate discrimination factors (DFs), which can differ among species and by physiological state. This thesis examined three questions using captive birds from the South African Foundation for the Conservation of Coastal Birds (SANCCOB). First, the effects of ontogeny on Î´13C and Î´15N ratios of African penguins (Spheniscus demersus) were assessed. Blood samples were collected from penguins in four age classes (P3 chicks, blues, juveniles and adults) concurrently with their diet (sardine (Sardinops sagax) and formula). Second, to assess the influence of breeding physiology on SI ratios, the blood of ten breeding pairs of penguins was sampled over a five-month period from June to October 2016. Following laying, each pair was categorised into one of three (four for whole blood) egg production phases (initial yolk deposition, rapid yolk deposition and post-laying) and their influences on SI ratios were tested. Third, species differences in DFs were evaluated for African penguins, kelp and Hartlaub's gulls (Larus dominicanus and L. hartlaubii), greater crested terns (Thalasseus bergii) and Cape cormorants (Phalacrocorax capensis). Flying birds were mostly fed sardine with a small but unknown amount of sardinella (Sardinella aurita), DFs were therefore estimated for a 50:50 sardine:sardinella diet, a 75:25 sardine:sardinella diet and a 100% sardine diet for each flying bird species. The DFs were assessed for the whole blood (WB), red blood cells (RBC), plasma (PL) and delipidated plasma of the penguins, and only WB for the flying birds as well as flesh, whole fish, delipidated flesh and delipidated whole fish for fish species, and for formula. Results indicated that age influenced both the Î´13C and Î´15N of WB, only the Î´15N of RBC and the Î´13C of delipidated PL. The assessment of breeding physiology yielded a significant interaction between the effects of egg production phase and sex on the Î´13C of WB; females had significantly lower Î´13C in the rapid yolk deposition phase than the other two phases and all males. The Î´13C of PL was affected only by sex, with females having a significantly lower Î´13C value than males. Neither physiological state nor sex influenced the other blood components. Differences were found among the three DFs in the non-penguin species, but not for all consumer "“ prey tissue combinations. There were also significant differences among species with a DF calculated from a diet with the most probable prey proportions eaten. Depending on the combination of consumer and prey tissue used to calculate the DF, a different conclusion regarding trophic information can be reached. A literature review updated with the present data showed that no general pattern or grouping of similar species with regards to DF values could be drawn, highlighting the importance of determining species- and tissue-specific DFs. Thus age, egg production, tissue and species all influenced the SI values of bird blood and therefore their DFs. Not all physiological conditions affect all blood components in the same way, making different components more or less sensitive to physiological influences. Though their influence is at a small enough scale that it is unlikely to hamper correct conclusion in ecological studies, it is crucial that these factors are considered when using SI analysis (SIA). When uncertainties exist for some coefficients in wild studies, SIA should therefore be combined to other dietary techniques to determine the food web structure as best as possible.
Keywords: Stable isotopes -- Analysis; African penguin -- South Africa; Breeding